Removal of alkali and transition metal ions from water with hydrophobic deep eutectic solvents. Issue 80 (19th September 2016) - van Osch, Dannie J. G. P.; Parmentier, Dries; Dietz, Carin H. J. T.; van den Bruinhorst, Adriaan; Tuinier, Remco; Kroon, Maaike C.
Abstract : Hydrophobic deep eutectic solvents composed of decanoic acid and lidocaine were used for the removal of metal ions from an aquatic environment. Abstract : Hydrophobic deep eutectic solvents were used for the first time for the removal of metal ions from non-buffered water. It was shown that the extraction occurs via an ion exchange mechanism in which all transition metal ions could be extracted with high distribution coefficients, even for high Co 2+ concentrations and low DES/water mass ratios. Maximum extraction efficiency could be reached within 5 s and regeneration was possible.